ANDROID-BASED RUSA (RUANG SISWA) LEARNING MEDIA WITH APPYPIE APPLICATION TO ENHANCE LEARNING MOTIVATION AND OUTCOME OF ANIMALIA MATERIAL OF GRADE X STUDENTS OF SENIOR HIGH SCHOOL: A RESEARCH AND DEVELOPMENT - Sugeng Riyanto; Dian Puspita Anggraini; Marinda Sari Sofiyana (JOSAR (Journal of Students Academic Research), 2019)
This research aims to identify the effect of RUSA (Ruang Siswa), an Android-based learning media with appypie application, and figure out the validity of the media to enhance motivation and learning outcome of grade X students in Animalia material. The method of this research was Pre-experimental. The type of (R&D). This development model applied Borg & Gall procedure which was limited up to the seventh step, that is, product revision. Based on the hypothetical test of the effect of RUSA (Ruang Siswa) on students’ motivation using t test, and the effect of RUSA on learning outcome using Ancova test, it was obtained that the significance value of RUSA (Ruang Siswa) was 0.000. Since the significance value was 0.000 < 0.05, H0 was rejected and H1 was accepted. Based on the result of validity test by media experts, the validity percentage was 74.50% classified as valid criteria, Material expert was 77.03% with classified as valid criteria, Language expert was 83.33% classified as very valid criteria. In addition, the data from students showed the percentage of 89.14% classified as valid criteria, and from the Biology teachers was 75.33% classified as valid criteria. Therefore, it is clear that there was an effect of using RUSA (Ruang Siswa) on students’ motivation and learning outcome. Referring to the validity result, RUSA (Ruang Siswa) is valid to use.